Case report Silent meningioma – a rare cause of stroke in post-cardiopulmonary bypass patients - Chow, Hon K.; Yousafzai, Sajjad M.; Ugurlucan, Murat; Canver, Charles C. (Archives of Medical Science, 2010)
Stroke in cardiac patients undergoing surgery is usually attributed to the use of cardiopulmonary bypass. In this report, we present an unusual cause of cerebral dysfunction: a meningioma leading to stroke, following coronary artery bypass grafting in a 62-year-old patient. Diagnosis and treatment options of the pathology are discussed with the guidance of the literature.